TUC election leaflet opposing the National Government, 1935 (1935)
1935 1918-1939 "TUC election leaflet opposing the National Government, 1935" [T0142.jpg], 1935, Labour Party The TUC urged the electorate to vote Labour to defeat the National Government led by Ramsay MacDonald. The Conservative Party won the election with 47.8% of the vote, the Labour Party came second with 38%.